2009
DOI: 10.1186/1477-7525-7-31
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of post traumatic stress symptoms and their relationship to professional quality of life (ProQoL) in nursing staff at a forensic psychiatric security unit: a cross-sectional study

Abstract: BackgroundViolence is frequent towards nurses in forensic mental health hospitals. Implications of this high risk environment have not been systematically explored. This paper explores occurrence of symptoms on post traumatic stress and their relationship to professional quality of life.MethodsSelf report questionnaires assessing symptoms of post traumatic stress and professional quality of life were distributed among psychiatric nurses in a high security forensic psychiatric unit with high frequency of violen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
118
5
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(139 citation statements)
references
References 14 publications
12
118
5
4
Order By: Relevance
“…Years in the profession has been negatively correlated with depressive symptoms in US nurses (Welsh, 2009). Conversely, having more than 20 years of experience in nursing has been associated with poorer mental health in Thai nurses (Kaewboonchoo et al, 2009) and with incidence of PTSD in Swedish forensic nurses (Lauvrud, Nonstad and Palmstierna, 2009). 5Age, experience and years In summary, multiple studies report higher prevalence of mental health problems and its correlates in younger nurses.…”
Section: Years In the Profession And Years In Rolementioning
confidence: 99%
“…Years in the profession has been negatively correlated with depressive symptoms in US nurses (Welsh, 2009). Conversely, having more than 20 years of experience in nursing has been associated with poorer mental health in Thai nurses (Kaewboonchoo et al, 2009) and with incidence of PTSD in Swedish forensic nurses (Lauvrud, Nonstad and Palmstierna, 2009). 5Age, experience and years In summary, multiple studies report higher prevalence of mental health problems and its correlates in younger nurses.…”
Section: Years In the Profession And Years In Rolementioning
confidence: 99%
“…6 In studies of the reasons employees remain in their role as caregivers despite high levels of compassion fatigue, findings indicated that the employees also gain a sense of compassion satisfaction, which is defined as the positive feelings derived from helping others through traumatic situations. [6][7][8] The cumulative experience of both compassion fatigue and compassion satisfaction is described as professional quality of life (ProQOL). 9 As conceptualized by Stamm, 6 a sustainable ProQOL is achieved by maintaining a healthy balance between the positive and negative aspects of caring.…”
mentioning
confidence: 99%
“…공감피로, 특히 이차 외상성 스트레스를 경험하는 개인은 공감으로 인한 고통으로부터 벗어 나기 위해 서비스 대상자에게 거리를 둠으로써 공감능력과 객관 적 시각을 모두 잃게 되며 이는 결국 업무 수행능력을 저하시키 기 때문이다 (Boyle, 2011). 그러므로 효과적인 간호업무를 위해 공감피로에 대한 관리가 중요하지만, 간호영역에서는 다른 직업 에 비해 공감피로에 대한 연구가 활발하게 이루어지지 못하였다 (Boyle, 2011 (Alexander, 2006Chase, 2005Frank & Adkinson, 2007Hooper, Craig, Janvrin, Wetsel, & Reimels, 2010Lauvrud, Nonstad, & Palmstierna, 2009Potter et al, 2010Robins, Meltzer, & Zelikovsky, 2009Yoder, 2010. Dominguez-Gomez & Rutledge, 2009Hooper, et al, 2010, 혹은 결혼상태를 분석하였으며, 직업관련 특성으로는 경력 (Lauvrud, et al, 2009), 근무 분야 (Hooper, et al, 2010Yoder, 2010, 스트레스 정도 (Abendroth & Flannery, 2006) …”
unclassified